Peran Citra Destinasi dan Nilai Altruistik Terhadap Minat Voluntourism - Nono Wibisono; Marceolla Suryana; Widia Senalasari; Rina Trisnawati (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2022)
This study aims to identify the role of destination image and altruistic values on voluntourism interest. The research method was used quantitatively using a questionnaire and data collected from as many as 347 respondents. The analysis technique used is descriptive analysis and Structural Equation Model (SEM), and the sampling technique used is purposive sampling. The results show that the state of nature, culture and history, tourist infrastructure, atmosphere of the place, and quality of service have a significant effect on altruistic values. Meanwhile, altruistic values have a significant effect on the wishes of tourist volunteers. Other findings, public infrastructure, economic factors, and tourist recreation have no significant effect on altruistic values. Based on the results of the study, it can be concluded that the image of the destination and altruistic values have a role to influence the desire for voluntourism.